Osoby samotne życiowo jako zjawisko społeczne - Żurek, Aldona (Wydawnictwo Naukowe UAM, 2003)
There has been a marked increase in single people living alone. In Poland about 17% persons live by themselves. This population is composed of divorced, widowed and never married. Most of them choose this life style because they questioned the notion that people must marry if they are to achieve happiness and well-being. Singles aren’t lonely people because they have wide relationships with friends, colleagues and members of family of orientations. The standards of life of single persons are better than those of other people.
Singlehood as a social problem